Secondary amine catalyzed retro-aldol reactions of enals and enones: one-pot conversion of enals to [alpha]-substituted derivatives - Enders, D.; Nguyen, Thanh Vinh (Pergamon, 2012)
A practical synthetic procedure to hydrolytically cleave the C,C-double bond of a,b-unsaturated aldehydes and ketones has been developed. Secondary amines are employed as organocatalysts for the retro-aldol process under simple and mild reaction conditions. Beside the generation of the parent aromatic aldehydes, the synthetic procedure has been successfully used in a one-pot reaction sequence to convert simple cinnamaldehydes into their a-aryl/alkyl substituted derivatives.